2020
DOI: 10.1186/s10020-020-00177-z
|View full text |Cite
|
Sign up to set email alerts
|

The α7 nicotinic acetylcholine receptor agonist, GTS-21, attenuates hyperoxia-induced acute inflammatory lung injury by alleviating the accumulation of HMGB1 in the airways and the circulation

Abstract: Background Oxygen therapy, using supraphysiological concentrations of oxygen (hyperoxia), is routinely administered to patients who require respiratory support including mechanical ventilation (MV). However, prolonged exposure to hyperoxia results in acute lung injury (ALI) and accumulation of high mobility group box 1 (HMGB1) in the airways. We previously showed that airway HMGB1 mediates hyperoxia-induced lung injury in a mouse model of ALI. Cholinergic signaling through the α7 nicotinic acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 80 publications
0
32
0
Order By: Relevance
“…GTS-21, is able to inhibit proinflammatory cytokines in vitro and in vivo and improve survival in murine endotoxemia and severe sepsis ( Pavlov et al, 2007 ). Hyperoxia-induced acute lung injury is attenuated by GTS-21 by inhibiting extracellular high mobility group box 1-mediated inflammatory responses ( Sitapara et al, 2020 ).…”
Section: How To Use the Anti-inflammatory Properties Of The Vagus Nermentioning
confidence: 99%
“…GTS-21, is able to inhibit proinflammatory cytokines in vitro and in vivo and improve survival in murine endotoxemia and severe sepsis ( Pavlov et al, 2007 ). Hyperoxia-induced acute lung injury is attenuated by GTS-21 by inhibiting extracellular high mobility group box 1-mediated inflammatory responses ( Sitapara et al, 2020 ).…”
Section: How To Use the Anti-inflammatory Properties Of The Vagus Nermentioning
confidence: 99%
“…Recently, our lab has reported that in mice exposed to 72 h of hyperoxia, 4 mg/kg i.p. administration of GTS-21 significantly attenuates the accumulation of HMGB1 in the airways and the circulation and mitigates inflammatory lung injury by decreasing the infiltration of neutrophils and inflammatory monocytes into the lung and the airways (Sitapara et al 2020 ). Thus, these data suggest that the activation of the α7nAChR with agonists, such as GTS-21 or nicotine, may represent a pharmacological approach to combat Gram-negative bacterial infections in organisms subjected to oxidative stress (Entezari et al 2012 ; Wang 1999 ; Ogawa et al 2006 ; Rowe et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both nicotine (a non-selective α7nAChR agonist) and GTS-21 inhibit endotoxin-induced NF-κB activation in macrophages (Wang et al 2003 ; Pavlov et al 2007 ). We have reported that NF-κB activation plays a critical role in hyperoxia-induced HMGB1 release (Wang et al 2015 ) and GTS-21 significantly decreases HMGB1 accumulation in the airways and the circulation in mice subjected to hyperoxia (Sitapara et al 2020 ). Hyperoxia-induced NF-κB activation in cultured macrophages and mouse lung cells is inhibited by GTS-21, suggesting the possible involvement of NF-κB in mediating GTS-21’s decrease of hyperoxia-induced HMGB1 release (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In severe COVID-19 cases an additional stimulation of α7-nAChR would be essential to restore the integrity of the immune system. A combination of α7-nAChR agonists along with the proposed antibody will definitely help regulate the proinflammatory cytokine concentrations, but whether that alone would suffice to restore the ability of the body to generate sufficient quantities of antibodies for a long term immunity requires further evaluation ( Sitapara et al, 2020 ; Andersson, 2020 ; Alexandris et al, 2021 ).…”
Section: Implications For Clinical Therapymentioning
confidence: 99%